Metabolites Profiling of Coffee Seeds in Context to their Origin, Processing and Gut Microbiota Interaction - Abdelwareth, Amr (AUC Knowledge Fountain, 2021)
Coffee is among the most consumed beverages worldwide, with the present study to focus on the aroma and non-volatiles composition associated with coffee seeds processing, brewing methods and gut microbiota interaction. The study uncovered a large number of primary and secondary metabolites in diverse coffee products consumed in the Middle East in the context of its origin, roasting, and blends and microbiota mediated biotransformation products. First, aroma of authentic coffee specimens of Coffea arabica and Coffea robusta alongside with commercial products consumed in the Middle East were analyzed using HS-SPME coupled to GC-MS and modelled using multivariate data analyses (MVA). Results revealed for 102 volatiles with a distinct aroma profile between the different brewing methods. Infusion demonstrated higher esters level, while decoction and maceration were more abundant in sesquiterpenes and terpene alcohols, respectively. Besides, heat-induced products, i.e., 4-vinyl guaiacol was identified as potential roasting index in instant coffee and roasted Coffea robusta brews. Blending with cardamom further masked the smoky odor of such chemicals by its fragrant terpinyl acetate. Second, non-volatile metabolites in coffee products analysis using GC/MS post-silylation led to the detection of 163 metabolites belonging to 15 different chemical classes. Fructose showed higher abundance in green Coffea robusta, while fatty acids i.e., palmitic and stearic acids were more abundant in Coffea arabica. Whereas, caffeine was found more abundant in roasted Coffea robusta compared to Coffea arabica. This study provides the first report on the chemical sensory attributes of Middle Eastern coffee blends and further reveal for the impact of brewing, roasting on its aroma composition. Lastly, insight into the microbiota mediated metabolism of black and green coffee brew is presented using in vitro culture and analyzed using GC/MS. Results present the first report regarding how coffee alter gut metabolism through either induction or inhibition of certain metabolic pathways, i.e. GABA production likely induced by coffee polyphenols. Likewise, functional food metabolites i.e., purine alkaloids acted themselves as direct substrate in microbiota metabolism.